Sweet potato flour, a new era in baking industry in Burundi - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
In Burundi, the Great Lakes Accelerated Innovation Delivery Initiative Rapid Delivery Hub (AID-I GLR) Project—locally dubbed Kugwiza Project (which means ‘to increase’ in Kirundi)—through its partnership with the International Potato Center (CIP) and local and international scaling organizations, including World Vision, Welthungerhilfe (WHH), One Acre Fund, CoopEden, and Cooperative Haguruka, is strengthening the orange-fleshed sweet potato (OFSP) value chain and changing livelihoods. The project introduced OFSP puree to the bakery industry to reduce the cost and enhance the OFSP demand.